HUBUNGAN UMUR IBU DAN KETUBAN PECAH DINI TERHADAP KEJADIAN BERAT BADAN BAYI LAHIR RENDAH - Inayati, Inna Noor; Pratami, Intan Monik; Resmi, Dewi Candra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Low Birth Weight Infants (LBW) are babies born weighing less than 2500 grams (up to 2499 grams). The results of document searches that have been carried out at Dr. M. Yunus Hospital are known in 2022 to have increased by 230 (23%) LBW babies (33 pure LBW and 193 premature LBW) from 1,045 babies. The purpose of the study was to determine the relationship between maternal age and premature rupture of membranes on the incidence of low birth weight. The type of research used quantitative research with case control design. The research was conducted at Dr. M.Yunus Hospital Bengkulu. The research was conducted in June 2023. The population was all newborns in 2020 at RSUD Dr. M.Yunus Bengkulu as many as 320 people, namely 106 LBW (72 premature LBW and 34 pure LBW). The sample consists of a case sample of 106 respondents and a control sample of 106 respondents. The sampling technique used total sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between maternal age (p value: 0.000) and early rupture of membranes (p value: 0.000) to the incidence of LBW. It is recommended that the Puskesmas and health workers can improve health services through ANC examinations at least 4 times during pregnancy so that early detection of factors associated with the incidence of LBW can be done. One of them is by screening mothers at risk, namely from the factors of age, parity, gestational age, and KPD that occur in pregnant women and conducting close supervision so that LBW births can be avoided.Keywords: Toddler, LBW, gestational age.